Clinical Research on Albumin-bound Paclitaxel-based Therapy in Advanced Lung Cancer - Xu LI (Chinese Journal of Lung Cancer, 2017)
Background and objective Albumin-bound paclitaxel is a novel paclitaxel formulation formed by the combination of paclitaxel and human serum albumin (HSA) to improve the efficacy of paclitaxel and reduce its adverse reactions. The aim of this retrospective study is to observe the efficacy and safety of albumin-bound paclitaxel-based therapy in the treatment of lung cancer. Methods We have enrolled 50 patients with advanced or unresectable retreatment lung cancer who were admitted from November 2011 to December 2014. All patients were treated with albumin-bound paclitaxel-based therapy with a 21 day cycle (albumin-bound paclitaxel weekly by intravenous dose of 130 mg/m2 on day 1 and day 8). Efficacy was evaluated every two cycles according to Response Evaluation Criteria in Solid Tumors (RECIST) 1.1 and side effects were observed during each cycle. All patients were evaluated. Results The total objective response rate (ORR) of albumin-bound paclitaxel-based therapy was 20%, disease control rate (DCR) was 68%. In the subgroup analysis, in squamous non-small-cell lung carcinoma groups, ORR and DCR were 26.7% and 80% respectively. Albumin-bound paclitaxel based chemotherapy combined anti-angiogenesis therapy had a promising overall response rate 36.4%. In the patients who had been previously treated with≥4 lines of chemotherapy DCR also reached 69.2%. The most common adverse reactions were hematologic toxicities and were all manageable, no hypersensitivity reactions or treatment-related grade 4 adverse events were reported. Conclusion Weekly albumin-bound paclitaxel is effective and well tolerated in the treatment of advanced lung cancer including all histological subtypes. Albumin-bound paclitaxel was associated with superior efficacy in patients with squamous (SCC) histology and combined with anti-angiogenesis therapy. Albumin-bound paclitaxel shown to be an effective and safe regimen for elderly or previous heavily treated patients.